Attitude Towards Research In Nursing Students Of A Public University 2023 - 2024 - Ambicho Da Cruz, Monica Briggeeth; Diaz Soriano, Ana Maria (Journal of Neonatal Surgery, 2025)
To improve professional practice and the quality of patient care, nursing research is essential. The present study sought to ascertain the prevailing attitudes towards research among nursing students at a public university, with the objective of identifying both strengths and weaknesses that could potentially influence their research training. A quantitative, descriptive, and cross-sectional design was employed, with a probabilistic sample of 196 nursing students. The "Attitude towards Research Scale" was employed as the data collection instrument, comprising 34 items and exhibiting a Cronbach's alpha coefficient of 0.854. The results indicated that 92.9% of the students exhibited a moderately favorable behavioral attitude towards research, while 86.7% demonstrated a moderately favorable affective attitude. Regarding the cognitive dimension, 61.7% of the students exhibited a favorable attitude towards research. In conclusion, nursing students exhibited a moderately favorable attitude towards research, suggesting the necessity to promote more research training strategies to enhance their participation and skills in this field.